Synthesis and Anti-Inflammatory Activity of New Alkyl-Substituted Phthalimide 1H-1,2,3-Triazole Derivatives - Shalom Pôrto de Oliveira Assis; Moara Targino da Silva; Ronaldo Nascimento de Oliveira; Vera Lúcia de Menezes Lima (The Scientific World Journal)
Four new 1,2,3-triazole phthalimide derivatives with a potent anti-inflammatory activity have been synthesized in the good yields by the 1,3-dipolar cycloaddition reaction from N-(azido-alkyl)phthalimides and terminal alkynes. The anti-inflammatory activity was determined by injecting carrageenan through the plantar tissue of the right hind paw of Swiss white mice to produce inflammation. All the compounds 3a–c and 5a–c exhibited an important anti-inflammatory activity; the best activity was found for the compounds 3b and 5c, which showed to be able to decrease by 69% and 56.2% carrageenan-induced edema in mice. These compounds may also offer a future promise as a new anti-inflammatory agent.